Introduction to Maxxam All-Season Passive Sampling System and Principles of Proper Use of Passive Samplers in the Field Study - Hongmao Tang (The Scientific World Journal)
Maxxam all-season passive sampling system (PASS) is introduced in this paper. The PASS can be used to quantitatively and accurately monitor SO2 , NO2, O 3, and H2 S in air in all weather conditions with flexible exposure times from several hours to several months. The air pollution detection limits of PASS are very low. They can be from sub ppb to ppt levels. The principles of proper use of passive samplers in the field study are discussed by using the PASS as an example.